Phase evolution and microstructure of complex-structured (1-x)PZT-xBDT ceramics - Thongmee N. (2014)
This study aims to fabricate and characterize a series of new complex-structured ceramics with formula (1 - x)Pb(Zr0.52Ti 0.48)O3-xBi3.25Dy0.75Ti 3O12 or (1 - x)PZT-xBDT (when x = 0, 0.1, 0.3, 0.5, 0.7, 0.9 and 1.0) using a solid state mixed oxide and sintering method. Optimum sintering temperature for this system was found to be 1000°C for 4 h dwell time. Phase analysis using X-ray diffraction indicated existence of BDT- as well as PZT-based solid solutions with corresponding lattice distortion. Scanning electron micrographs of ceramic surfaces showed plate-like structure in BDT-rich phase while typical grain structure was observed for PZT-rich phase. PZT-rich ceramics also possessed high densities due to their more equiaxed grains with high packing capability compared to the ceramics with addition of plate-shaped BDT. © 2009 World Scientific Publishing Company.